Perception Regarding Tooth Carving Using wax Block among the Dental Practitioners - Lamichhane, Ram Sudhan; Chaulagain, Rajib; Pradhan, Amita; Khadka, Suman (Journal of Nepal Health Research Council, 2022)
Background: The various pedagogical methods applied for teaching dental anatomy to dental students includes lectures, analysis of extracted natural teeth and carving of wax blocks to accurately replicate the morphology of teeth. The thorough knowledge of dental morphology is indispensable for a successful dental practice. This study was thus aimed to assess the perceived relevance of tooth carving using wax block among the dental practitioners.Methods: A cross-sectional study was designed with the objective of involving dental practitioners working in Kathmandu. Self-administered questionnaires were used for the data collection. The results were later analyzed for descriptive statistics using the Statistical Package for the Social Sciences (SPSS) 16 software.Results: About 232 (98.3%) participants practiced tooth carving using wax block to study dental anatomy. More than 96% of the participants agreed that tooth carving exercises have helped them better understand tooth morphology and more than 85% feel that their manual dexterity was developed by these exercises. A total of 223 (94.5%) were of the opinion that tooth carving should be continued in the BDS preclinical curriculum.Conclusions: The dental wax carving is an effective pedagogical strategy to develop manual dexterity of dental students by recreating tooth morphological features using a wax block, thereby achieving the mandatory psychomotor skills. Keywords: Dental students; dental specialities; questionnaires survey